Supply Chain Risk Control Strategy for Aircraft Maintenance in the Era of the Covid-19 Pandemic - Ahmad Rifai; Stefanus Budy Widjaja Subali (Asosiasi Peneliti Manajemen Adat Indonesia, 2022)
Aviation is an industry that has been severely impacted by the COVID-19 pandemic. Several number of risks arise due to the low demand for flights which results in a number of business risks, including obstacles that occur from the SCM side of the aircraft maintenance industry. This study aims to analyze risk control strategies in supply chain management, by offering updates in the evaluation of SCOR using the Supply Chain Operations Reference (SCOR) model version 12, House of Risk (HOR), and pareto diagram.The object of research is PT GMF Aero Asia, which is an aircraft maintenance service provider (MRO). This research is a qualitative-phenomenological type using primary and secondary data. Primary data was obtained from interviews with informants who represented managerial in the field of SCM at GMF Aero Asia, while secondary data was obtained from documentation studies by collecting documents related to the research. The data obtained is then processed according to the stages of risk identification, risk severity analysis, risk probability, and risk management. The results showed that there were 50 risk events, including 7 risk events from the SCM planning process (planning), 9 risk events from the source procurement process (source), 11 risk events from the production operation process (make), 12 events risk from the delivery process, 7 risk events from the product return process (return) and 5 risk events from the maintenance & compliance process (enable), as well as 30 risk triggers (risk agent). Other results state that there are 9 risk agents that will be prioritized for preventive action.